DEVELOPMENT OF HIGH SCHOOL COMMERCIAL CURRICULUM AND UNIVERSITY COURSES. - Prickett, A. L. (The Accounting Review, 1928)
Abstract The article focuses on the problem of curriculum construction, which has been constantly with the education system in the U.S. ever since educators many years ago felt the necessity of formulating a definite program. The problem is pressing and stupendous right now because of certain changes in the industrial and social fabric. After close contact with a score or more of the leaders in commercial work both in the secondary and in the college divisions, one approaches the intricate subject with due humility. Certain factors well known to all have created a situation calling for new diagnosis. Among the more evident changes are, industrial progress; progress in distribution whereby place utilities are created; the perfecting of distinct functions such as financing, purchasing, storing, personnel; changes In social life; great increase in school enrollments; changes in the philosophy and doctrines of education and in their application. In the development of curricula over a period of time, subjects do not maintain a stable position but shift up or down. As these courses have moved downward, they either remained unchanged in scope of content or expanded.